2023
DOI: 10.3389/fneur.2023.1202631
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter retrospective study of patients treated in the thalamus with responsive neurostimulation

Madeline C. Fields,
Onome Eka,
Cristina Schreckinger
et al.

Abstract: IntroductionFor drug resistant epilepsy patients who are either not candidates for resective surgery or have already failed resective surgery, neuromodulation is a promising option. Neuromodulatory approaches include responsive neurostimulation (RNS), deep brain stimulation (DBS), and vagal nerve stimulation (VNS). Thalamocortical circuits are involved in both generalized and focal onset seizures. This paper explores the use of RNS in the centromedian nucleus of the thalamus (CMN) and in the anterior thalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The thalamus is increasingly considered a useful target to investigate both for the treatment of epilepsies that were previously considered “non-surgical,” such as primary generalized epilepsy and Lennox-Gastault and for seizures that involve eloquent regions that are not amenable to ablative or resective techniques. Because of the broad convergent-divergent nature of the cortico-thalamo-cortical system, the thalamus can be a target for neuromodulation to palliate debilitating seizures, including in patients with impairment of consciousness where cortico-thalamic circuits are implicated [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus is increasingly considered a useful target to investigate both for the treatment of epilepsies that were previously considered “non-surgical,” such as primary generalized epilepsy and Lennox-Gastault and for seizures that involve eloquent regions that are not amenable to ablative or resective techniques. Because of the broad convergent-divergent nature of the cortico-thalamo-cortical system, the thalamus can be a target for neuromodulation to palliate debilitating seizures, including in patients with impairment of consciousness where cortico-thalamic circuits are implicated [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Just as the accurate lesioning of SgRFTC may be utilized to target fiber tracts, it may also be advantageous for sparing functional tracts and thereby limiting neurological morbidity; Song et al [55] have recently illustrated the utilization of diffusion spectrum imaging tractography to complement SgRFTC in optic radiation-sparing interventions. Another opportunity for precise lesioning by SgRFTC builds on current evidence for the role for neuromodulation of thalamic structures [56,57] in the generalized epilepsies. Preliminary data from Aguado-Carrillo et al [58] have suggested a palliative role of radiofrequency ablation of the centromedian thalamic nucleus.…”
Section: Future Of Sgrftcmentioning
confidence: 99%